Agent-oriented methodologies - Henderson-Sellers, Brian; Giorgini, Paolo (Idea Group Pub, 2005)
"The book presents, analyzes and compares the most significant methodological approaches currently available for the creation of agent-oriented software systems"--Provided by publisher.